Pengaruh Inklusi Keuangan Dan Literasi Keuangan Terhadap Keputusan Menjadi Nasabah - muhammad dzulkifli wakit (edujavare, 2024)
Financial inclusion and financial literacy have become a major focus in modern financial studies. In this context, this scientific article aims to investigate the influence of financial inclusion and financial literacy on an individual's decision to become a customer at a financial institution. By understanding the factors that influence individual decisions in utilizing financial services, this research provides valuable insights into developing policies and strategies to increase participation in the financial system and strengthen individual financial resilience. In an effort to understand the impact of financial inclusion and financial literacy, this research uses a quantitative approach and statistical analysis to explore the relationship between these variables and an individual's decision to become a customer. The research results show that financial inclusion and financial literacy have a significant influence on individuals' decisions regarding their participation in financial institutions. This research provides a new contribution to our understanding of the role of financial inclusion and financial literacy in shaping individual financial behavior. The policy implications resulting from these findings can help in strengthening the financial system, increasing the accessibility of financial services, and advancing the overall economic well-being of society